Investigation of the stress-strain state during new combined deformation technology - Volokitina, I.E.; Panin, E.A.; Volokitin, A.V.; Fedorova, T.D.; Latypova, M.A.; Makhmutov, B.B. (Karagandy University of the name of academician E.A. Buketov, 2025)
This paper presents the results of finite element modeling of a novel technology of combined deformation by radial-shear broaching and traditional drawing. Using DEFORM program, the parameters of stress-strain state and deformation forces were studied. A range of models with varying initial diameters of the workpiece, single and total compressions, and different temperatures of heating the workpiece were considered. It was revealed that the optimal conditions occurred at 30-25-20 scheme at a temperature of 900°C. However, this scheme can be recommended when the strength of the deforming equipment is sufficient. In other cases, it is necessary to select a scheme that allows for deformation without exceeding the limiting loads.
Keywords: drawing; modelling; bar; steel; stress-strain state